ChemInform Abstract: Nuclear Spins as Spies to Explore the Structure of Materials. Issue 19 (18th April 2013) - Babonneau, Florence; Bonhomme, Christian; Gervais, Christel; Azais, Thierry; Laurent, Guillaume; Lafon, Olivier; Montagne, Lionel; Trebosc, Julien; Delevoye, Laurent; Tricot, Gregory; et al., et al.
Abstract Review: 33 refs.